The practices of hope : literary criticism in disenchanted times - Castiglia, Christopher (New York University Press, 2017)
At a moment when the "hermeneutics of suspicion" is under fire in literacy studies, The Practices of Hope encourages an alternative approach that, rather than abandoning critique altogether, relinquishes its commitment to disenchantment. Catiglia instead offers hopeful reading, a combination of idealism and imagination that retains its analytic edge yet moves beyond nay-saying to articulate the values that shape our scholarship and create the possible worlds that animate genuine social criticism. Drawing on a variety of critics from the Great Depression to the Vietnam War, from Granville Hicks and Constance Rourke to Lewis Mumford, C.L.R. James, Charles Feidelson, and Richard Poirier, Castiglia demonstrates that their criticism simultaneously denounced the social conditions of the Cold War United States and proposed ideal worlds as more democratic alternatives. Organized around a series of terms that have become anathema to many critics - "nation," "liberalism," "humanism," "symbolism"--The Practices of Hope shows how they were employed in criticism's "usable past" to generate alternative critiques: practices of hope. -- Provided by publisher